Distance between root apices and the floor of the maxillary sinus and its relation to the skeletal pattern facial - Garcia-Rosas, Brenda (2020)
Objective. To determine the distance between root apices of premolars and upper molars to the floor of the maxillary sinus and their relationship with the skeletal pattern. Methods. A cross-sectional study that included 75 orthodontic pre-treatment cases from the files of patients who attended the Orthodontic Postgraduate Course at the Autonomous University of Nayarit, México. The skeletal pattern of the patients was determined through digital lateral cephalometric radiographs and according to the Angle classification they were grouped in Class I, Class II and Class III. The distances between the apices of the second premolars, first and second upper molars and the floor of the maxillary sinus were measured on cone beam CT scans. The software Ez3DPlus Version 1.2.6.0 (Vatech, Gyeonggi-do, Korea) was used. Data analysis was performed using the Student t-test. Results. Significant differences were found between the Class II (Mean= 1.338; Sd=1.852) and Class III premolars group (Mean= 3.26; Sd= 3.941), (p=0.031). Conclusions. The results obtained in this study showed that the skeletal pattern was not a determining factor in the distance of the root apices of upper molars to the floor of the maxillary sinus. However, the differences found between the second premolars of Class II and Class III could be due to this variable.